Evaluation of Comparative Efficacy of Ashwagandha (Withania somnifera) vs Brahmi (Bacopa monnieri Linn) on Stress Level and Quality of Sleep in the Subjects Experiencing Mental Stress: A Clinical Trial Protocol - Mohnish Vijay Gokhale; Vaishali Kuchewar; Pankaj Yadav; Bhishmani Tarare (Journal of Clinical and Diagnostic Research, 2025)
Introduction: Adequate sleep is essential for the preservation of both physical and mental health. Sleep deprivation or interruption can cause a variety of physical, metabolic and cognitive problems, resulting in stress, anxiety, obesity and other neurocognitive dysfunctions. Sleep deprivation causes loss of sleep-dependent processes in the hippocampus and pyriform cortex, which are responsible for memory and perception. N eed of the Study: Everyone in today’s world has stress and insufficient sleep as a result of their work load, hectic lifestyle, adoption of sedentary habits and other factors. Ayurveda has described many herbs under ‘medhya rasayan’. Ashwagandha is commonly used than Brahmi. Brahmi is relatively easy to cultivate and inexpensive, hence this study is planned. Aim: To study the comparative efficacy of Ashwagandha (Withania somnifera) vs Brahmi (Bacopa monnieri Linn) on stress level and quality of sleep in the subjects experiencing stress. Materials and Methods: It is a double-blind standard control clinical trial and the study will be undertaken at Department of Kayachikitsa, Mahatma Gandhi Ayurved Hospital and Research Centre (MGACHRC) at Salod (H), Wardha, Maharashtra, India starting from January 2024 to June 2025. This study will include 60 patients (30 in each group) experiencing mental stress. Group-A (Experimental Group) and Group-B (Control Group) will be given Brahmi ghana (extract of Bacopa monnieri Linn) and Ashwagandha ghana (extract of Withania somnifera), respectively with Luke warm water at bed time for 60 days. The patients will be assessed on every 15th day through Perceived Stress Scale (PSS) and Pittsburgh Sleep Quality Index (PSQI) scales.